Antimicrobial Peptide NK-2 as an Emerging Therapeutic Agent: A Study with Phospholipid Membranes. (2019) - Karmakar, Sanat; Maity, Pabitra; Halder, Animesh
Abstract: An antimicrobial peptide, NK-2, derived from a cationic core region of NK-lysin, is known to display antimicrobial activity towards negatively charged bacterial membranes. The aim of the present study is to get insights into the mechanism of antimicrobial activity. We have prepared unilamellar vesicles as model membranes composed of bacteria mimicking lipid composition. The interaction of NK-2 with phospholipid membranes has been investigated using a variety of experimental techniques, such as, isothermal titration calorimetry (ITC), zeta potential, dynamic light scattering (DLS). NK-2 exhibits strong binding affinity towards the negatively charged membranes, which indeed a characteristic of bacterial membrane. The weak binding affinity towards the neutral phospholipid suggests that NK-2 is expected to be inert towards normal eukaryotic cells. The ITC results show the overall endothermic response in the heat signal, suggesting the entropic contribution in the lipid –NK-2 interaction. One site binding model given by microcal origin, has been used to estimate the intrinsic binding constant and other thermodynamic parameters of binding kinetics of NK-2. The proliferation of size distribution of negatively charged vesicles containing NK-2 indicates the presence of large aggregates. Summarizing all experimental observations, we have suggested a possible mechanism of antimicrobial activity of NK-2.